Nutritional assessment of pre-school children in rural village of the family dynamics, lifestyle and nutrition study (1997-2001) - Chee, Heng Leng; Khor, Geok Lin; Arshad, Fatimah; Wan Muda, Wan Abdul Manan; Shabdin, Ahmad Affendi; Abu Samah, Asnarulkhadi; Abdullah, Rohani; Bidin, Siti Jamilah; Emby, Zahid; Mohd Marjan, Zamaliah (Persatuan Pemakanan Malaysia, 2002)
This paper presents the socio-economic profile of households in the Family Dynamics Study (FDS) (1997-2001) and makes comparisons with the earlier Functional Groups Study (FGS) (1992-1996). For the current study, FGS villages with a high prevalence of child malnutrition were purposively selected. In each village selected, all households were included, and interviews with a structured questionnaire were conducted in April-May 1998. Incomes were generally low and incidence of poverty was high; 49.6% of the households were under the poverty line income, of which 37.2% were poor and 12.4% were hard core poor. Overall, only 23.2% of heads of households were in agricultural occupations, others being primarily waged workers and petty traders. Livestock rearing was widespread (57.8%), and most households (90.4%) owned at least one motorized vehicle, the most common being the motorcycle. The majority of households had refrigerators (73.6%), washing machines (58.8%), and televisions (91.1%); but telephones (42.2%), mobile phones (6.1%) and computers (2.3%) were less common. Although 99.7% of households had electricity supply and 95.1% had either a flush or pour flush latrine, only 57.4% had piped water supply. In comparison to the FGS, poverty in the current study is lower (49.6% of FDS households are poor compared to 55.2% of FGS households), the proportion of household heads in agricultural occupations is also lower (26.9% compared to 55.3%), while all other socioeconomic indicators were better, except for piped water supply, which remains inadequate for households in the current study.